Server Room Temperature Remote Monitoring System - Tamayo, Josan D.; Reyes, Angelo M. (Future Science / FSH-PH Publications, 2024)
The COVID-19 pandemic creates more significant opportunities to develop more Internet of Things-based systems. IoT has been helpful in remote monitoring and control of connected devices. This research aims to develop a Room Temperature Remote Monitoring System using an Arduino Board and Cloud storage. It provides remote room temperature monitoring, real-time reports and graphs, and a 3-way alert/alarm system when the observed temperature is out of range. The prototype developed is compared to the room thermometer and provides accurate results.